Home economics education development opportunities - Kūla-Braže, Elīna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In relation to the ongoing changes in the sphere of education in Latvia based on a sustainable development of education, concerns about the sustainability of the education of home economics in the circumstances of a changing environment have become deeper. On the basis of the ecological approach new development potentialities for the improvement of the education of home economics have been formulated – the development scenario, the applied arts scenario and the scenario of the home environment economics. The target of these scenarios is harmonious development of the student’s individuality, inheriting the cultural properties, creative activity in the development of the cultural environment and development of the quality living space. The scenarios were worked out on the basis of experience of the formal education and non-formal learning in the development of the subject of home economics as well as on the basis of interaction of the educational environment and cultural environment.